ANALISIS PENGARUH LINGKUNGAN KERJA, KOMUNIKASI DAN FASILITAS KERJA TERHADAP SEMANGAT KERJA PEGAWAI KANTOR PERTANAHAN KABUPATEN PONOROGO - Yuswa Dolar Tri Sendik Aksa; Woro Utari; Mei Indrawati (Badung: LPPM Universitas Triatma Mulya, 2021)
The purpose of this study was to describe the work environment, communication, work facilities, and morale at the Ponorogo Regency Land Office, to determine and analyze the influence of work environment, communication and work facilities on employee morale of the Ponorogo Regency Land Office. The population in this study were 93 employees of the Ponorogo Regency Land Office. The number of samples used in this study were 93 people. The data collection techniques used were questionnaires and documentation. The data analysis technique used Multiple Linear Regression. Based on the research results, it can be seen that the variables of communication, work facilities and morale in the Ponorogo Regency Land Office are in good categories, only work environment variables are in the good enough category. Work environment, communication and work facilities have a significant effect on the morale of employees of the Ponorogo Regency Land Office.